Integrating Artificial Intelligence (AI) into the Think-Pair-Share Cooperative Learning Model to Enhance Elementary School Students’ Collaborative Skills - Aditya Sita Dewi; Novaria Jannah; Ika Putri Rahayu (Universitas Negeri Surabaya, 2026)
The development of Artificial Intelligence (AI) technology has opened new opportunities for innovation in elementary education, particularly in fostering 21st-century skills. This study aims to describe the effect of integrating AI into the Think-Pair-Share (TPS) cooperative learning model on elementary school students’ collaborative skills. The research employed a quantitative method with a causal associative approach, in which the TPS model was combined with AI-based media support during the think, pair, and share stages. Research instruments included questionnaires, observation sheets, and documentation to measure teachers’ responses, students’ activities, and collaborative skills. The findings indicate that the implementation of the AI-assisted TPS model enhanced active participation, shared responsibility, and mutual respect within groups. Observational data revealed a significant increase in student engagement, with collaborative skills reaching 96% on the mutual respect indicator. Both teachers and students expressed highly positive responses toward the effectiveness of AI integration in supporting the learning process. Therefore, the AI-based TPS cooperative model can serve as an innovative alternative for improving collaborative skills in elementary schools.